صراع الدول الأوروبية الكبرى على الأراضي الألمانية "1742-1745" - حزيم، حسن زغير; زينل، زهرة زين العابدين (الجامعة المستنصرية - كلية التربية, 2017)
يعد الصراع بين الدول الأوروبية الكبرى على الأراضي الألمانية خلال(1742-1745) من الحروب الكبيرة والخطيرة بين هذه الدول التي حاولت أن تثبت لها موضع قدم ونفوذ في هذه الأراضي الاستراتيجية وبالأخص بروسيا وفرنسا فالأول كان ملكها يعمل لإبراز قوته وقوة دولته في نظر الدول الأوروبية من خلال كسب المقاطعات الغنية التابعة للإمبراطورية النمساوية وبالأخص في تلك الأراضي، والثاني يريد إضعاف سلطة آل هابسبرك في الأراضي الألمانية من خلال دعم بعطن المقاطعات الألمانية الطامحة في عرش الإمبراطورية الرومانية المقدسة بالأخص أمارة بافاريا ومقاطعه سكسونيا، وبدأت الحرب بانتزاع فرنسا العرش الإمبراطوري من بيت هابسبرك بعد تتويج امير بافاريا شارد إلبرت امبراطورا للامبراطورية الرومانية المقدسة باسم شارل السابع ،فرفضت ملكة النمسا ماريا تيريزا هذا الانتخاب وأعلنت الحرب على إمارة بافاريا أمام هذا الأمر شكلت فرنسا وبروسيا وامارة بافاريا ومقاطعه سكسونيا تحالف قوي ضد النمسا وبريطانيا، فدخلت هذه الأطراف في نزاع شديد فيما بينهم استمرت مدة اربع سنوات خسرت خلالها الاطراف المشاركة ضحايا بشرية كبيرة واثرت على الناحية الاقتصادية والعسكرية لهذه الدول والامارات والمقاطعات. The conflict of the Great European powers(1742-1745)over the German Lands is regarded as one of the biggest and most dangerous wars amony these great powers that attempted to gain a zone of influence in those strategical German lands ^specially Prussia and France. The King of Prussia worked to show his power and the power of his coumtry to the European powers through gaining the rich province belonged to the Austrian empire,while the king of france wanted to weaken the power of Hapsburg in the German lands through supporting some German provinces that aspire to get the throne of the holy Roman empire especially the princedom of Ravaria and province of Saxony. The research divided into an introduction, five parts and a conclusion .The first part is about( the election of European powers and countries about his election) while the second part is about (Breslau convention and the Prussian getting out from war) The third part concerned with (the continuation of war between Austria , france and the princedom of Bavaria till worms convention in 13 September 1743, The fourth part is a bout (the war in the German lands in 1744) in the fifth part a discussion of (the end of war in the German lands in 1745). The conflict of the greet European powers (1742-1743)showed superiority and success of the Prussian army in the German lands agoinst the armies of Austria and its allies who lost many lands and many men while their resources were weakened. The death of Charles VII in 1745, was an Important Point in the Changing the Countries Policy's Course. It Contributed to Effect on French and Prussia's Policy, the main Supporters of Bavaria Cause they Lose their Pretext to Continue the War, as they had Lose the Basic Justification which were Based on to Support Charles VII. This had Formed a Lightening point for Austria because that May Return the Holy Roman Empire throne to Hapsburg House after the Concession of Charles VII's son of Claiming the throne
Keywords: تاريخ ألمانيا -- الأراضي الألمانية -- الدول الأوروبية